The Effectiveness of Jogging Sprint Combination Training on Students Fat Levels - Santika, I Gusti Putu Ngurah Adi (Universitas Negeri Semarang, 2020)
At this time teenagers tend to do less exercise as a routine activity due to technological developments that tend to make teenagers more engaged in gadgets. By being lazy to move and continuous intake of food will accumulate fat levels in the body. Based on this, it is necessary to do exercises that aim to reduce the level of body fat, namely the jogging sprint combination. The research sample consisted of 24 people divided into 2 groups, namely the treatment group and the control group. The research design was Experimental Randomize Pres-Test and Post-Test Group Design. The results showed that there was a decrease in the level of body fat levels in the jogging sprint combination training with an average decrease in the level of body fat levels by 6.7% or by (23.26%). The conclusion of this study is that the jogging sprint combination training can reduce the level of body fat levels male student X MIPA public senior high school number 2 Tabanan.